PENATAAN PASAR TRADISIONAL, PUSAT PERBELANJAAN DAN TOKO MODERN STUDI KASUS KECAMATAN ROWOSARI KABUPATEN KENDAL - Mujiono, Untung; Sari, Suzanna Ratih; Rukayah, Siti (Jurnal Arsitektur ARCADE, 2020)
Seeing the very important role of traditional markets for the community, it is necessary to examine several things that can affect the smoothness or success in increasing people's income. Therefore, to improve and maintain the role of traditional markets, there needs to be involvement or coordination with agencies to support the welfare and success of traditional market traders. So, in this study, the location was taken by considering the welfare of the traditional market in Rowosari Village. There is a traditional market that has been around for a long time and is managed by the village government. Descriptive method is used in this research which explains the situation in Rowosari Traditional Market. From the results of the study, Rowosari Traditional market plays a role in increasing the income of the community who generally come from the Rowosari region and surrounding areas.Â